Shadow banking a prawo karne gospodarcze - Ochman, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The article attempts to answer the question whether in the current legal state theactivity of shadow banking in Poland is subject to criminalization. The limits and scope of criminalization of entities of this element of the fi nancial market is also presented. The reflections are supplemented by a review of the defi nition of parallel banking, and also discussed the economic crimes that can be traced back to parallel banking activities.
Keywords: prawo karne gospodarcze; równoległy system bankowy; bankowość równoległa; nielegalna działalność finansowa